THE USE OF INNOVATIVE TECHNOLOGIES IN THE FORMATION OF PROFESSIONAL COMPETENCES OF GRADUATES OF ARTISTIC INSTITUTIONS OF PROFESSIONAL HIGHER EDUCATION (Innovative professional education, 2025)
The article deals with the actual issues of using innovative technologies in the educational process of students in artistic implementing professional pre-higher education institutions. The main tasks of a competitive specialist in the labor market are defined, meeting the needs of the globalized modern environment while taking into account the possession of reguired skills, including social competencies
Keywords: innovative technologies, professional competencies, labor market, specialist, personality, globalized environment